Dinâmica fenológica e atributos morfofuncionais de populações de uma espécie arbórea neotropical (maprounea guianensis aubl.) em florestas úmidas e secas - Santos, Marília Grazielly Mendes dos (2020)
This study analyzed the amplitude of the variability of the functional traits of Maprounea guianensis in wet and dry forests in Chapada Diamantina, contrasting in soil characteristics and water availability. It is presented in three chapters, the first analyzed how different environmental conditions affect the leaf habit, investigating the intrapopulational phenological diversity, seasonality and longevity of the leaves; the second analyzed the morphofunctional traits in terms of responses to seasonal drought and the adaptability of the plant; and the third verified the effects of drought on vegetative growth, associating radial increase, phenology and water potential. In the first chapter, the phenophases of budding and leaf fall were observed monthly in 62 trees marked between 2004 and 2012 (84 months) in sites of humid (cloud, gallery, tableland) and dry (seasonally dry tropical forest - SDTF). From this data, leaf longevity was calculated to identify leaf habit, seasonality was analyzed by circular statistics, phenological diversity and the correlation of phenophases with precipitation and photoperiod. In the second chapter, ecophysiological measurements were carried out between January/2017 to April/2019, in 5 individuals/site to assess water potential, succulence, thickness and densityleaf, in the dry and rainy seasons; basic wood density and saturated water content of the wood were evaluated in the rainy season. Precipitation and soil moisture were monitored monthly, analysis of the physical properties of the soil was performed. The functional traits were subjected to analysis of variance. Phenotypic plasticity indices (PPI) at each site were calculated to comparing the averages by the analysis of variance. In the third chapter, in this last period, the radial increase and vegetative and reproductive phenology were followed monthly in the gallery forest and SDTF in 22 individuals/site. Through cross correlation, the radial increment was compared with the phenology and precipitation and photoperiod data. A T test analyzed exchange activity and phenophases between sites. The results showed seasonality and low intraspecific diversity in vegetative phenophases. The longevity of the leaves was more reduced in the dry forest, and there was a variation in the evergreen to deciduous habit. M. guianensis demonstrated low water storage capacity in its leaf and woody tissues, variations in water potential and high phenotypic plasticity. Precipitation and photoperiod were triggers for foreign exchange activity, and for the appearance of budding, flowers and fruits. Our results highlight the plants responses to drought regimes. We show the importance of associating functional traits to the water availability in M. guianensis strategies, which, due to their high plasticity, can modulate escape or tolerance strategies to the water deficit period.